Oral history interview with Evangelos Stathis / Interviewee Stathis, Evangelos Interviewer Molho, Renna Date interview: 2015 June 26 Language Greek Extent 1 digital file : MPEG-4. Credit Line United States Holocaust Memorial Museum Collection, courtesy of the Jeff and Toby Herr Foundation (United States Holocaust Memorial Museum, 2015)
Interviewee Stathis, Evangelos Interviewer Molho, Renna Date interview: 2015 June 26 Language Greek Extent 1 digital file : MPEG-4. Credit Line United States Holocaust Memorial Museum Collection, courtesy of the Jeff and Toby Herr Foundation: Beep Three two one Ready Good morning I want to thank you for accepting meet us again to talk thank you very much Tell me your name and the subject Evangaylos Stathis When were you born and where were you born? In the village here, in Perama, in 1926. Do you remember that we had talked together again a month and a half ago, that we had met? So, if something escapes us that you will not remember, I will remember it for you. I want you to tell me a little about your family, what your father was doing, about your siblings, tell me. My father was in charge of... he was in charge of helping the sick people here in the village. Something like a nurse? Yes, a nurse. And he did other things too, he was in charge of agriculture and so on. What was his name? Ilias Stathis. And what siblings did you have? Sisters? Sisters? I didn't have any sisters, I had one brother. What was his name? He has left, he went to Athens and so on, and he came back and we were here. What was his name? His name was Dimitris. Does he still live? Does your brother still live? No. Where did you go to school? Here in Perama. Did you go to Ioannina when you were young? Did you go to Ioannina? To Ioannina? Yes. I did. For what reason? If you don't go to Ioannina, let's say, let's say you didn't stay in the village, we wanted to go to the cinema, to a shop, let's say, to Cyprus. And when you finished high school? Yes. What did you do after that? When I finished high school, I took care of Agilades. Meaning? I went and took care of her in the fields where I used to graze her, because the fields were here and there, so they couldn't get to the places. Not near any fields? In any area here in Perama? Here in Perama. What changed in your life when the war started? In your own life? I was here when, before the soldiers came, they gave me the gun and said, let's go and guard the village here, because the guerillas were going to the mountains and so on. And then, let's say, when my age came for me to join the army, they took me from here and took me to Serras. There I went and was trained, let's say, and I became a mercenary. I had two mules, I loaded them, we went from here to there, and so on. And in the meantime, when we were there on that hill, we went to the army and so on. When did you go as a soldier? Before the war? Before the war, did you go as a soldier? The war, let's say, was from earlier, but I went to... how can I say, it was a little thing. Did you go as a soldier? No, it was a little resistance, they didn't have the strength. And later, when they had the strength, I went over there and was trained, I had two mules, and we went, let's say, in battle, from here to there. After what happened? After you were trained? I was trained and I took the mules, both of them, and loaded them in battle, and we went to Monadis, where it was on the hills. Was this happening while the war was going on? Or was it after the war? It was after the war. Where did the war find you? When I was fired from the infantry, how can I say, from the infantry, when they called me a soldier and I spent so many months there, I went to Serras. Yes, you told me that. But this happened after the liberation. When the civil war happened, when did this happen? No, later, later. Later. I want you to tell me about before. When the Germans and the Italians came here, I want you to tell me about that period. Where did the occupation find you? The occupation was here, in Pera. Tell me a few things. Did you meet Jews in Ioannina? How? Did you know them? What? Did you know them? I didn't know them. They had shops. Do you remember any names? No. Didn't they help you? No, because I went to an ideal place, which was down here, in front of the pier, and there was a sugar factory, and I went there to work. Here in Pera or in Ioannina? In Ioannina. In Ioannina. Yes. And the man who owned the sugar factory, was he a Christian or a Jew? He was a Christian. Don't you remember what they used to say when you were a child about the Jews here in Pera? The Jews were not here in Pera. They were in Ioannina. But as children, did your grandparents or mothers tell you anything about the Jews? Of course, a little. What did they tell you? Let's see, so we don't take it too seriously. They told me not to leave here, because the Jews would take you and put you in the cellars, and you would be dragged to hell. Yes. When did you see Jews for the first time? When I went to Ioannina. And then you were here until the war was declared. Yes. Did you see any Jews here in Pera at any point? No. Because the previous time you said that you had seen the trucks that took the Jews. The trucks, the cars, yes, they had passed from here. What could we do? The Germans took them, of course. How close were you? We were where Platon is now. There were three or four Platons in front of us. The trucks passed by and the Germans started talking to them. How many trucks did they have? I can't tell you the truth. They passed by, let's say a few, because the Jews took most of them. How did you know that they were Jews? How could I not know? I was in high school, in Ioannina. What did you see on the trucks? What did these people do? They said, where are they taking us? I don't know. Give it to me. And they said, let's say, they cried, let's say, let's say, the women. Because they took both women and men. Were the trucks open? And did you see them? Yes, the trucks were open. Open? Did you remember what month it was? I don't remember. And who was driving the trucks? It was the driver. We were in the car. These cars were political, not military. Did anyone keep these trucks? Yes, there were soldiers, let's say. Which soldiers? Soldiers from various units. Were they Greeks? Were they Germans? What were they? What were the soldiers? Where from? What language did they speak? Our language, let's say. Were they Greeks? Yes. Did they speak Greek? They spoke Greek, of course. Because I think that last time you said they were Germans. The Germans came later. They came later? Yes. That is, the Greeks gathered the Jews? They were... The Greeks gathered the Jews? The Greeks gathered the Jews... What can I tell you? I wasn't there to tell you. I don't know how they got the Jews. We were there to go to the cars. Did you see them on the cars? Where would they take us? The women from here told me. Did you see anyone on the trucks? Any of those you knew from Ioannina? Let me tell you, as soon as I saw them, I left. Why? Because the Germans came and took me to the cars. The Germans took you? Yes. Did anything like that happen? Did they go to get any... No, let's say... Christians? No, they sat down. I sat down to say a few... some twenty-something pounds. And when I saw that they were forced to go and gather people and so on, I left. Do you remember who was guarding the trucks? And how were they guarding them? The trucks were up there. There were a few soldiers. There were two, three, five of them. In the front or in the back? In the front, in the back. They didn't go into the vehicles, they didn't go into the trucks. And what were they guarding them with? What were the soldiers guarding them with? The soldiers had weapons. They had weapons. What else were they wearing? Except for weapons? Their uniforms. They went up, let's say, and they went through here. And did you see the trucks stopped or did you see them moving forward? I saw them moving forward, they didn't stop. And you said you sat down for twenty minutes and left? Yes. Were there others around you who were watching? There were others here, others there, let's say, and they were guarding them. What did the guards say? Why did the Jews send them? Did they know what the Jews would do to them? Where did they go? How would they know? They say that the Jews, the Germans, let's say, I don't know which part, they made a big fuss about it, and that's why they had these guns and they shot them all. There were many who ran away, let's say, and stayed here in Greece. Apart from the Jews, how did the Germans bring them to the Christians? To the Christians? They didn't bother. Why did they scare them? They didn't bother, let's say, the Christians. Why did you scare them then? I wasn't scared of them. I was here. I wasn't in Ioannina when the Jews left. When they made a fuss about going to the cars. After the Jews left, did you go to Ioannina at all? Wherever they wanted me to go, I went. What did you see in Ioannina? The houses, the shops of the Jews, what happened? They died. They died? Yes. Didn't someone else take them? Later, what happened, let's say, they locked them up with the state, they took them to the cars, the Germans, and they went up to Macedonia, I don't know where they went, and I don't know who executed them. But the things from their houses, where did they leave them? Of course. Who took them? There were people, don't be afraid. There were people who were poor, so they took them home. I don't know, it's been many years now, to tell you exactly what happened. Did you see anyone who took things from the houses of the Jews? Did you see anyone like that? No, I didn't go there. Did you see any Christian things inside the houses of the Jews? You know what happened, let's say, the Germans were there, they told us, the Jews were passing by, so we went down there, we came to the pier, I had a boat of my own, so I came here. And I saw them here, because they took hours to gather them all. And when they passed from here, I saw them going to the cars. Do you want to say, if I understood correctly, that the Christians in Ioannina were afraid and left? No. Who came to the pier? I was in the pier. Ioannina was open, everything. They weren't afraid, let's say. They knew that they would be taken by the Jews. Didn't you tell me, did anyone from Ioannina come, after the Jews left, to sell things here? The Jews? No, the Christians? No. Didn't they come to the pier? They came to the pier, but let's say something old-fashioned, they were lost there, from what I saw, but I went to say why. I had a boat, and when I left, I was in the fields, outside, and the boats were boating. And in the shops of the Jews that you knew, did you see other people there, in Ioannina? They took them from the houses there, because the Jews were organized, let's say. They weren't among the citizens, let's say, the Greeks, and so on. Then, the shops? Who took them? The Greeks took them, let's say. There was no one, let's say. Now, there was, let's say, the state, from whom I knew, let's say, and they kept the houses, and so on. The state employees? After the war ended, the liberation, did you see Jews returning to Ioannina? I saw the Jews returning to Ioannina after that, but I don't know if they were the same ones who had the houses. Did you recognize them? No, I didn't recognize them. They came, let's say, now, let's say, because they had relatives, but let's say in Athens, I don't know, yes. I mean, they were just relatives, you didn't know if they were relatives. Do you have anything else to tell me about that period when you remember it? Either from Ioannina, or from the experience? What should I remember? Yes, I say, maybe you remember, and I didn't ask you. Tell me something, from the time of the war, where do you want to tell me? Look, you see, when I saw, let's say, over there, I was in Ioannina. There was a sugar factory down there, in Kormanio. And from there I took, I had my own boat, and I came to Perama. And 160 cars passed from here to the top, let's say, the Germans. I understood that you were next to the trucks, with the boats, that you went close. I was close, when they were there in Livadi, which was where they were digging, it was from the inside, from the road. How close were you? How many meters? I was in Livadi, it was a few hundred meters inside. Were there others with you, who were watching? No, no. I was the only one there. Wasn't your brother with you? My brother was younger. Ah, he was younger. Yes, of course. Thank you very much, Mr. Stathis. Yes. I will ask some of my colleagues, if they have any other questions. Oh, of course. Cut. Cut. Let's go. Mr. Stathis, you had started to tell me that you remembered something when the Jews were being loaded into the trucks. What did you remember? Where I was? Where? Where there was a sugar factory in Kormanio, where the vegetables were being bought. I had gone with my grandmother to go with the vegetables, with the boat, and I left her there, because there was a sugar factory over there, and we knew each other there. We went, we ate a sweet with a friend, and from there we came back and we took the boat and came from Stavro. It was from Stavro. What did you see in Kormanio? The Germans were there and they were collecting the Jews. Can you tell me what you saw when they were collecting them? They were crying, they were saying voices, noises, from here and there and so on. Did you see how they were being loaded into the trucks? Of course. That's why I took the boat and left. I didn't want the Jews to pass by and take them. That's why I left. Can you tell me what you saw when you went to the boat in Livadi? Where in Livadi? Where you went to the boats in Geladia. Did you see the boats being loaded into the trucks? Yes, there was a field down here, and they were trying to take us from the road. So you saw them again? I saw them again from the other side. And you saw them crying? Yes. And what were they saying? What were they saying? They were crying. They were being loaded into the trucks. In the back of the cart. So it was open for you to see them? Of course. Can you tell me something? You said that you saw some people who had some things after the Jews left, and they came to the pier and sold them. What were those things? I didn't see them. I was going to go to Seras, and he came with his car and took me there. And I was there at his shop. I don't care about Seras. I care about the pier and Janina. Did anyone come to the pier to sell things after the Jews left? To sell what? To sell clothes and so on? Yes. I haven't seen them. You didn't see them. They might have stolen some things, because there were no people from the pier. I didn't see them. I didn't see them. Thank you very much, Mr. Stathi. Cut. Three, two, one, stop. Ready. Mr. Stathi, I want you to think about that day when you went to the pier with your grandmother, and you saw the Germans loading people into the trucks. Let's stop there for a moment. How did you realize that these people were Jews? The Jews? They were all grown up, and they were full of people. How did you know that they weren't Christians? The Jews? No, the ones who gathered, that they were Jews. When the Germans went there, they went with the trucks. Where did they go? Where the convent was. That's what I want to know. At the convent? Yes. Have you seen the convent? I've been there many times. The Germans were foreigners. How did they know who the Jews were in the convent? Were only the Jews there? No, they were Christians. But they were some of the first to go there. Did you see anything with your own eyes? Where could I see? I was just down there where the sugar factory was. Excuse me. I left. I want to ask you, when did you go with your grandmother? What time in the morning did you go with your grandmother to the sugar factory? They didn't have a grandmother. My grandmother was at home. You went alone? Alone. What time was it? Was it morning? It was morning. It was about ten o'clock. Ten o'clock. Maybe more, because they didn't have a clock. Tell me something. Then you said that you were afraid that they would take you and you left. And I left, of course. What did you see and were you afraid? They gathered us all together, men and women. How did the Germans treat you? The Germans were worse. They were all looking at me from one side. Tell me something. When you went to the sugar factory with the boat, did you see the trucks again? I saw the trucks passing by. What time was it? Was it afternoon? Was it noon? What time was it? I don't know what time it was. But it was the same day? Yes, the same day. And did you see them? Did the trucks pass by when you saw them? Were they stopped? No, because they were passing by on the road, as it is. They were pulling me up. And someone asked me what time it was. And I told him that I went to Janna and I saw the boat and I left without wanting to. Out of fear? Of course. It was a shame, the Germans, to tell you that there were people in Janna who were shooting at them and so on and so forth. It was not something to say that they were cruel people. Did you know any Jews before? Well, let's say now that we met there at the port, we knew some, yes. Can you tell me a little bit about when they loaded them into the cargo ship? Yes, yes. In what detail did you see who was in the cargo ship? I didn't see them at all. When they told me that it was the Germans and that they were coming to take them, people left and it was a dead end over there where the German trucks had stopped. After you returned to the port and the Jews left with the cargo ships, did you say that you saw two men who were selling things? No, I didn't see them. You didn't see them? They said that they were going to tell me what they were selling, but I didn't see them. Thank you very much.